Development of Problem-Based Daily Face Makeup Module for Vocational Higher Education - Gusmelidawati Gusmelidawati; Rahmiati Rahmiati (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2022)
Daily makeup is a material that is learned in basic beauty subjects that must be mastered by students of the beauty program of Vocational Higher Education. This study aims to develop daily makeup teaching materials in the form of daily makeup modules using a problem-based learning model. In this study, the validity and practicality of the development results will be measured. This research is a type of research and development research and development (R&D), in this study, it is necessary to follow the predetermined stages starting from the Define, Design, Develop and Disseminate stages by providing modules to educators to be used as teaching materials in the classroom. The data collection instrument used in this study was a Likert scale questionnaire as a validation assessment to material and media experts as well as practicality tests from students and educators, and data analysis using percentages with predetermined categories. The research sample was class X students of the beauty program of SMK Negeri 6 Padang, totaling 3 students for a small group test before entering the practicality test, 18 students for the practicality test, and one educator. The results obtained are 1) the development has been carried out with a 4-D development model which produces a problem-based daily makeup module, 2) the results of the module validation analysis by material experts obtain an overall rating percentage of 87% with the category